(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: cancer pain is still undertreated as for inappropriate use of opioids, as for reason related to other factors. To increase knowledge of cancer pain, the “Mario Negri” Institute promote a series of initiatives to improve the quality of care and patients’ outcomes. Methods: a series of activities were launched including literature review, clinical studies and training schemes. Results: literature reviews shown a prevalence of undertreatment ranged from 8% to 82% and a raw prevalence of BTcP (Breakthrough Cancer Pain) of 51%. In the outcome research study mean worst pain at baseline was 6.8, and 38.3% received a strong opioids. Prevalence of BTcP was 40.3%, and 33.9% of the patients were not receiving rescue therapy at the study inclusion. About analgesic effectiveness of oral and transdermal opioids (TD), treatments with TD were associated with a lower probability to switch (OR=0.83) and to drop out from the study (OR=0.68). Conclusions: the initiative, still ongoing, has allowed a) the creation of a unit for the study and evaluation of cancer pain, b) the production of clinical evidence about the epidemiology, quality and effects of cancer pain management in Italy, c) the design and promotion of a Randomized Controlled Trial to evaluate the effectiveness of four major opioids.